Autophagy in Viral Infection and Pathogenesis - Liang, Shan; Wu, Yun-Shan; Li, Dong-Yi; Tang, Ji-Xin; Liu, Hua-Feng (Frontiers in Cell and Developmental Biology, 2021)
As an evolutionarily conserved cellular process, autophagy plays an essential role in cellular metabolism of eukaryotes as well as in viral infection and pathogenesis. Under the physiological conditions, autophagy is able to meet cellular energy needs and maintain cellular homeostasis through degrading long-lived cellular proteins and recycling damaged organelles. Upon viral infection, host autophagy could degrade invading viruses, initial innate immune response and facilitate viral antigen presentation, all of which contribute to prevent viral infection and pathogenesis. However, viruses have evolved a variety of strategies during the long evolutionary process, by which they could hijack and subvert host autophagy for their own benefits. In this review, we highlight the function of host autophagy in the key regulatory steps during viral infections and pathogenesis and discuss how the viruses hijack the host autophagy for their life cycle and pathogenesis. Further understanding the function of host autophagy in viral infection and pathogenesis contributes to scientists and clinicians to develop more specific therapeutic strategies to fight against various infectious diseases, such as the epidemic coronavirus disease 2019.